Terminalia catappa as a Novel Biosorbent for the Removal of Divalent ion from Aqueous Solutions: Experimental Investigation - Muthulakshmi, A. N.; Anuradha, J. (Novel Aspects on Chemistry and Biochemistry Vol. 1, 2023)
The effectiveness of acid-treated Terminalia catappa seed shell (TTCSS), an agricultural waste, for the adsorption of Cu(II) from aqueous solutions is highlighted in the current work. Adsorbent dose seems to have a great influence on sorption process. A significant risk to human health results from the Cu(II) effluent from industry spreading into the environment through soil and water streams and accumulating along the food chain. Fourier Transform Infrared (FTIR), Scanning Electron Microscopy (SEM), and Energy Dispersive X-ray Analysis (EDAX) analyses are used to characterize TTCSS. For the Cu(II)- TTCSS system, batch equilibration method experiments were performed to determine the effect of operating factors such as particle sizes and doses of the adsorbent material, agitation time between the sorbent and the sorbate species, temperature, and pH of the medium. The following parameters have been shown to be the most effective for removing Cu2+ ions (92%) from an initial concentration of 8mg/L : 0.18 mm particle size, 50mg adsorbent dose, 60 min contact time and pH 7. It is discovered that the highest adsorption capacity (Ce) of Cu(II)(7.122mg/g) is higher than the range of 2.1-5.2 mg/g as documented by other researchers for various sorbent materials. This demonstrates Terminalia catappa's superior sorption capacity, when compared to the other materials under study.